NON-DESTRUCTIVE, REAL-TIME, AND AUTOMATIC MEASUREMENT OF TRANSPIRATION FROM A PLANT CANOPY STAND (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
This study to measure plant canopy stand transpiration was conducted using newly developed sensor units. Transpiration from the tomato stand and by artificial leaves made of towel and paper filters showed good agreement with data measured by weight loss using a weighing device. The problem of sun flecks directly on the back side of the sensor causes malfunction of the energy balance equation, which is the basis of this method when LAI is not dense. During the period when a sun fleck was on the sensor, the data were eliminated. Overall measurements of this kind are far superior to measurements taken using a leaf porometer to estimate transpiration from the entire plant canopy stand.